Synthesis of carbon nanotubes with controllable diameter by chemical vapor deposition of methane using Fe@Al2O3 core–shell nanocomposites. (18th May 2020) - Wu, Shan-Luo; Chen, Chun-Ming; Kuo, Jia-Hong; Wey, Ming-Yen
Graphical abstract: Highlights: Carbon nanotubes were produced by nanocomposites during methane cracking. The pore size of the shell can be changed with the CTAB concentration. Carbon nanotube with a tunable diameter ranged from 19 nm to 58 nm. The carbon nanotubes have a complete graphite structure. Abstract: A novel and simple synthetic approach toward core–shell Fe@Al2 O3 nanocomposites were developed in this study. The as-synthesized catalyst was applied to convert the methane into carbon nanotubes. Moreover, due to the properties of the core–shell structure, the amount of surfactant can be adjusted to control the pore size of the shell and further control the diameter of the carbon nanotubes. In this study, the conversion of CH4 was up to 97% and the carbon production was 135 mgC /gcat. *h, which is much higher than traditional supported catalysts under similar reaction conditions. In addition, the carbon product quality (IG /ID ) was up to 1.96. The enhanced CH4 catalytic activity for the core–shell Fe@Al2 O3 catalyst originated from the combined acidic sites on the surface of the Al2 O3 shell and the high carbon diffusion rate of the Fe core, which led to the high efficiency of CH4 conversion and longer lifetime of the catalyst.